Bibliometric analysis of the Green Deal policies in the food chain - Dorin Vicenţiu Popescu; Adriana Dima; Elena Radu; Ecaterina Milica Dobrota; Victor Marian Dumitrache (Amfiteatru Economic Journal, 2022)
Nutrition concerns and food waste are a priority for the European Union, and the implementation of Green Pact policies is of major interest to all those involved in the food chain sector. The main purpose of this paper is to conduct an in-depth analysis of scientific production using bibliometrics, to understand the current structure of studies and future research directions on Green Deal policies in the food chain. 672 documents published between 2000 and 2021 were identified in the Web of Science database. Their scientific content was analysed using VOSviewer software on several levels: descriptive analysis, performance analysis, and scientific mapping from a conceptual, intellectual, and social perspective. In addition, to determine research gaps, the 10 most relevant and influential papers are analysed and synthesized. The most productive countries in terms of scientific output are Italy, India, and the USA, the peak being reached in 2021, and the main field approached is environmental sciences. Most of the articles analysed are reviews, highlighting gaps in primary research on Green Deal policies in the food industry. In this regard, several future research directions in the field are proposed.
Keywords: Q18; 330; bibliometric analysis; circular economy; farm to fork; food chain; food waste; Green Deal; sustainable development.